2016
DOI: 10.1017/s0022215116008252
|View full text |Cite
|
Sign up to set email alerts
|

Balloon dilation for eustachian tube dysfunction: systematic review

Abstract: Background: Eustachian tube dysfunction is a disorder for which there are limited medical and surgical treatments. Recently, eustachian tube balloon dilation has been proposed as a potential solution.Method: A systematic literature review was performed. Abstracts were selected for relevance, and pooled data analysis and qualitative analysis was conducted.Results: Nine prospective studies, describing 713 eustachian tube balloon dilations in 474 patients (aged 18-86 years), were identified. Follow-up duration ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 19 publications
1
37
0
Order By: Relevance
“…BET has emerged as a new minimally invasive intervention used for the treatment of ETD [15,16]. In this study, we developed an image-guided navigation balloon catheter to be used during BET to treat ETD.…”
Section: Discussionmentioning
confidence: 99%
“…BET has emerged as a new minimally invasive intervention used for the treatment of ETD [15,16]. In this study, we developed an image-guided navigation balloon catheter to be used during BET to treat ETD.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent systematic review examining balloon dilatation for eustachian tube dysfunction was performed in 2016. 9 Five of the studies in that review were included in the current analysis. [23][24][25][26][27] The authors identified 9 prospective studies that included 474 patients and 713 balloon dilatations with a follow-up duration ranging from 1.5 to 18 months.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Schröder et al 23 reported improvement in tube scores from 3.13 (±2.47 SD) to 5.75 (±2.76 SD) after 1 year and 2.65 (±2.89 SD) to 6.26 (±3.07 SD) after 2 years. 23 A recent meta-analysis by Hwang et al 20 reported favorable outcomes after ETBD in which 7 studies assessed improvement in Valsalva or Toynbee maneuver from 20 (8%) preoperatively to 177 (72%) out of 245 ears following ETBD. Six studies [24][25][26][27][28][29] used tympanograms as their outcome metric and found that in preoperative ears, 7 out of 141 ears (5%) had a type A tympanogram, as compared to 86 out of 141 ears (61%) postoperatively.…”
Section: Discussionmentioning
confidence: 99%